Pengaruh Foreign Direct Investment, Inflasi dan Nilai Tukar Terhadap Kinerja Ekspor Manufaktur di Indonesia - Dewi Sulfiana; Sri Ulfa Sentosa (Universitas Negeri Padang, 2021)
This research aims to determine the impact of foreign direct investment, inflation and exchange rates on the export performance of the Indonesian manufacturing industry. This type of research is a quantitative, descriptive and pertinent research method. The data used is the secondary annual time series data from 1980 to 2019, it will be obtained from relevant institutions. This study uses the multiple linear regression analysis model and the OLS (Ordinary Least Square) method to determine the influence of the independent variables on the dependent variables. The results of this study also show that foreign direct investment, inflation, and exchange rates have a significant impact on the performance of Indonesia's manufacturing exports. In addition, some: (1) Foreign direct investment has a positive and significant impact on the performance of Indonesian manufactured exports; (2) Inflation has a positive and significant impact on the performance of Indonesian manufactured exports; (3) Exchange rate There has been a positive and significant impact on the performance of Indonesian manufactured exports.